Targeting miR-148b-5p Inhibits Immunity Microenvironment and Gastric Cancer Progression - Zhang, Yuyu; Huo, Wei; Sun, Lidi; Wu, Jie; Zhang, Chengbin; Wang, Huanhuan; Wang, Bin; Wei, Jinlong; Qu, Chao; Cao, Hongshi; Jiang, Xin (Frontiers in Immunology, 2021)
Background: MicroRNAs (miRNAs) have been discovered to dictate the development of various tumors. However, the roles of miRNAs in the progression of gastric cancer (GC) is still lacking. Methods: Herein, by analyzing GC cell lines and patients samples, we observed that miR-148b-5p was significantly downregulated in GC. We also confirmed that miR-148b-5p overexpression significantly inhibited GC cells proliferation and invasion in vitro and in vivo. Results: Overexpression of miR-148b-5p not only reprogrammed the metabolic properties of GC but also regulated the immune microenvironment by shifting lymphocyte and myeloid populations. Mechanistically, ATPIF1, an important glycolysis-associated gene, was identified as a direct target of miR-148b-5p and mediated the effect of miR-148b-5p. Notably, low level of miR-148b-5p was significantly related with poor prognosis of GC patients. Importantly, the levels of miR-148b-5p significantly changed the sensitivity of GC cells to several anti-cancer drugs. Conclusions:Targeting miR-148b-5p inhibits immunity microenvironment and gastric cancer progression.